The Atacama Large Millimeter Array (ALMA) : Implications of a Potential Descope - National Research Council (U.S.) (Online access: National Academy of Sciences National Academies Press.)
"Executive Summary: The Committee to Review the Science Requirements for the Atacama Large Millimeter Array conducted a study to evaluate the consequences of a descope of the Atacama Large Millimeter Array (ALMA), which is intended to be the major, ground-based observational facility for millimeter and submillimeter astronomy for the next three decades. The committee was asked to consider the scientific consequences of reducing the number of active antennas from 603 to either 50 or 40 antennas. The committee concluded that: · A 60-element array would be greatly superior to any current or planned comparable instrument for several decades and would revolutionize millimeter and submillimeter astronomy. · Two of the three level-1 requirements, involving sensitivity and high-contrast imaging of protostellar disks, will not be met with either a 40- or a 50-antenna array. It is not clear if the third requirement, on dynamic range, can be met with a 40-antenna array even if extremely long integrations are allowed for. · Speed, image fidelity, mosaicing ability,4 and point source sensitivity will all be affected if the ALMA array is descoped. The severest degradation is in image fidelity, which will be reduced by factors of two and three with descopes to 50 and 40 antennas, respectively. · Despite not achieving the level-1 requirements, a descoped array with 50 or 40 antennas would still be capable of producing transformational results, particularly in advancing understanding of the youngest galaxies in the universe, how the majority of galaxies evolved, and the structure of protoplanetary disks, and would warrant continued support by the United States. · Furthermore, it is the committee's appraisal that a 40-antenna array would retain ALMA's strong support within the general astronomical community. However, the rapid decline in imaging capability that would result with a further reduction below 40 antennas would erode this support. 3Although the plan is to construct 64 antennas, only 60 will be operational at any one time. Likewise the committee assumes that 50- and 40-antenna arrays will require the construction of 54 and 44 antennas, respectively. 4Mosaicing refers to the mapping of areas larger than the field of view of a single antenna, by using multiple pointings, up to a thousand in extreme cases."